2018
DOI: 10.3389/fmicb.2018.02113
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Disinfectants on Bacterial Aerosol Diversity in Poultry Houses

Abstract: To better understand the effect of different disinfectants on the types and quantities of microorganisms in a broiler chicken house, five different types of disinfectants, including ozone, available chlorine, quaternary ammonium salt, glutaraldehyde, and mixed disinfectant, were used. The broiler house microbial communities were analyzed by high-throughput sequencing combined with air sampling. The results showed that the concentrations of airborne aerobic bacteria in the empty broiler houses after application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 63 publications
4
23
0
Order By: Relevance
“…While alcohol gave the smallest zones of inhibition against the test isolates, the total absence of inhibition zone in presence of alcohol was previously reported [ 40 ]. Besides, similar to our findings, the efficacy of alcohol based disinfectants tested by the same method was also reported below the satisfaction level previously [ 31 ]. Hence, the reason could probably be a limitation of the testing method itself, as alcohol, being volatile, might have evaporated before it got into contact with the test organisms.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…While alcohol gave the smallest zones of inhibition against the test isolates, the total absence of inhibition zone in presence of alcohol was previously reported [ 40 ]. Besides, similar to our findings, the efficacy of alcohol based disinfectants tested by the same method was also reported below the satisfaction level previously [ 31 ]. Hence, the reason could probably be a limitation of the testing method itself, as alcohol, being volatile, might have evaporated before it got into contact with the test organisms.…”
Section: Discussionsupporting
confidence: 91%
“…An effective sanitation plan for biosecurity of the poultry is based on the appropriate selection of disinfectants, which should consider the contaminants present and their sensitivity to the available disinfectants [ 31 ]. While among diverse microorganisms of poultry origin, the streptococci-micrococci group of bacteria is one of the predominant contaminants of poultry representing about 35% to 92% of the total poultry contaminants [ 8 , 15 , 31 ], no data for these organisms have been reported from the poultry sector of Bangladesh, let alone the efficacy of the commonly used disinfectants against the organisms. Therefore, the current study targeted this group of poultry microbes and found that S. lentus was more prevalent (32/102, 31.37%) than micrococci including M. luteus (7/102, 6.86%) and M. aloeverae (4/102, 3.9%).…”
Section: Discussionmentioning
confidence: 99%
“…Proper use of disinfectants can help contain and prevent the spread of these pathogens from inanimate objects. However, the study has revealed resistance of some microorganisms on a different type of disinfectants [ 18 ]. A study done by Guimarães et al [ 19 ] on different disinfectants revealed that bacteria resistance to phenols and quaternary ammonium compound ( qac ) was common.…”
Section: Introductionmentioning
confidence: 99%
“…It has been used extensively in the food industry (specifically water treatment, washing of produce, and food preparation), as well as in domestic restoration to remediate odors and smoke damage. Its historical use and proven efficacy demonstrate its potential to remediate contaminated indoor air (50,51). This would present a novel application of a known treatment modality.…”
Section: Research and Development Of Mitigation Strategiesmentioning
confidence: 99%